SYLLABUS-BASED EFL PROGRESS TEST FOR PRIMARY SCHOOL CHILDREN - Sevinchoy Soatboyeva Madamin qizi; Sobirova Gulnoza Xidirboyevna (TADQIQOTLAR, 2025)
Annotation: This article discusses how to design syllabus-based progress tests for primary school EFL learners. It explains the benefits of testing what students have learned in class and offers simple, practical ideas for creating fair and age-appropriate tests.